2019
DOI: 10.3390/cancers11030326
|View full text |Cite
|
Sign up to set email alerts
|

Role of miRNAs in Melanoma Metastasis

Abstract: Tumour metastasis is a multistep process. Melanoma is a highly aggressive cancer and metastasis accounts for the majority of patient deaths. microRNAs (miRNAs) are non-coding RNAs that affect the expression of their target genes. When aberrantly expressed they contribute to the development of melanoma. While miRNAs can act locally in the cell where they are synthesized, they can also influence the phenotype of neighboring melanoma cells or execute their function in the direct tumour microenvironment by modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 185 publications
(256 reference statements)
4
64
0
Order By: Relevance
“…Analysis of whole-exome sequencing data revealed only a few mutations previously identified as associated with acquired resistance to targeted drugs. It is in line with the current view that in parallel to genetic alterations, melanoma cell-autonomous mechanisms of resistance can rely on complex transcriptomic adaptations supported by epigenetic regulations, including miRNA-mediated mechanisms, and extended by the interplay between tumor and stromal cells that involves cell-cell interactions, paracrine stimulation and extracellular vesicles to create a resistance-permissive niche [39][40][41][42][43][44][45][46]. Mechanisms of resistance primarily directed to support proliferation and survival of cancer cells implicate a plethora of transcriptional regulators, adaptive responses, and feedback loops that extensively affect melanoma cell phenotype enabling the expansion of distinct cell subpopulations in the presence of drug(s) [27,[47][48][49][50][51][52].…”
Section: Discussionsupporting
confidence: 83%
“…Analysis of whole-exome sequencing data revealed only a few mutations previously identified as associated with acquired resistance to targeted drugs. It is in line with the current view that in parallel to genetic alterations, melanoma cell-autonomous mechanisms of resistance can rely on complex transcriptomic adaptations supported by epigenetic regulations, including miRNA-mediated mechanisms, and extended by the interplay between tumor and stromal cells that involves cell-cell interactions, paracrine stimulation and extracellular vesicles to create a resistance-permissive niche [39][40][41][42][43][44][45][46]. Mechanisms of resistance primarily directed to support proliferation and survival of cancer cells implicate a plethora of transcriptional regulators, adaptive responses, and feedback loops that extensively affect melanoma cell phenotype enabling the expansion of distinct cell subpopulations in the presence of drug(s) [27,[47][48][49][50][51][52].…”
Section: Discussionsupporting
confidence: 83%
“…In addition, a loss of functional PTEN (phosphatase and tensin homolog) and enhanced activity of the PI3K (phosphatidylinositol 3-kinase)/AKT/ mTOR (mechanistic target of rapamycin kinase) pathway, a suppression of BIM (BCL-2 interacting mediator of cell death), a loss of STAG2 (stromal antigen 2) or STAG3 (stromal antigen 3) that are the subunits of cohesion complex, an increase in cyclin D1 level, enhanced expression of several microRNAs, and expression of resistance-associated genes including AXL, PDGFRB (platelet-derived growth factor receptor beta) and EGFR (epidermal growth factor receptor) have been demonstrated to contribute to resistance of melanoma cells. In addition to cell-intrinsic mechanisms, growth factors derived from stromal cells and hypoxia can modulate melanoma cell sensitivity to targeted drugs [10][11][12][14][15][16], and long-term therapy with BRAF V600E inhibitor can develop resistance to other drugs including dacarbazine [17]. Resistance to immunotherapy can also emerge, and melanoma cells resistant to PD-1 inhibitors show upregulation of receptors VISTA (V-domain Ig suppressor of T cell activation) and TIM-3 (T-cell immunoglobulin and mucin domain-containing…”
Section: Introductionmentioning
confidence: 99%
“…Many studies revealed that the expression of several miRNAs is deregulated in melanoma cells and that aberrant miRNA expression is undoubtedly linked to important processes affecting tumor formation and progression [35,36,[84][85][86][87][88][89][90][91]. One example are members of the let-7 miRNA family which are involved in melanoma invasiveness [92], cell cycle promotion [93] and metabolism [94].…”
Section: The Role Of Mirnas In Melanoma and Hepatocellular Carcinomamentioning
confidence: 99%
“…Further risk factors for melanoma development are family predisposition [80] as well as multiple occurrences of melanocytic nevi (which are benign proliferations of melanocytes in the skin and can be transformed to precursor lesions of melanoma) [81]. In advanced/metastatic disease, systemic first-line therapeutic options are specific BRAF-inhibitors for BRAF V600E -mutated melanomas [82] as well as immune checkpoint inhibitors [83] but the understanding of emergence of acquired resistance to these therapies is still an unmet clinical need.Many studies revealed that the expression of several miRNAs is deregulated in melanoma cells and that aberrant miRNA expression is undoubtedly linked to important processes affecting tumor formation and progression [35,36,[84][85][86][87][88][89][90][91]. One example are members of the let-7 miRNA family which are involved in melanoma invasiveness [92], cell cycle promotion [93] and metabolism [94].…”
mentioning
confidence: 99%